RESOURCE SYNERGY OF NETWORK COOPERATION OF ENTREPRENEURIAL STRUCTURES: FACTORS AND CONDITIONS OF ACHIEVEMENT - STADNYK, VALENTYNA; HRYZOVSKA, LILIJA; GADZHUK, MAKSYM (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article highlights the problematic aspects of the functioning of business structures of Ukraine in the war and the future recovery period, It is emphasized that maintaining their viability requires new models of economic cooperation. They must meet the paradigm of the knowledge economy and ensure the achievement of sustainable development goals. In their organizational basis, new business models should be based on the potential of human interaction in the creation and use of new knowledge that can be embodied in competitive products and services in the global market. It is argued that such models of economic cooperation are network business partnerships, which are formed by integrating business structures along the chains of consumer value. The advantages of network business partnership in two spheres are systematized: direct resource supply and formation of organizational conditions for achieving resource synergy. Emphasis is placed on changing the dispositions of participants within the organizational shell of the business network - an individual participant is transformed from a resource (a means by which the desired result is achieved in the chain of consumer value) to a business development partner. Understanding by network members of their role in ensuring the effectiveness of the created business model determines their organizational behavior, makes it competitive. This contributes to the accumulation of an important intangible resource to achieve resource synergy - network organizational capital. The conditions under which the business network will be stable and efficient are indicated. They belong to the motivational function of management and provide an assessment of the valence of the motives of the participants. It is necessary to ensure the effectiveness of cooperation, in which the motivation of participants to develop overall competitiveness will outweigh the motivation of separate management.